Frequency of Hyponatremia in Gastroentric Patients Treated with Intravenous Hypotonic Fluid - Badeli, Hamidreza; Golshekan, Kioomars; Shahrdami, Moslem; Azizi Asl, Mohammadreza; Hassanzadeh Rad, Afagh (Journal of Pediatric Nephrology, 2013)
How to Cite This Article: Badeli HR, Golshekan K, Shahrdami M, Azizi Asl MR, Hassanzadeh Rad A. Frequency of Hyponatremia in Gastroentric Patients Treated with Intravenous Hypotonic Fluid. J Ped. Nephrology 2013 July;1(1):23-27. Introduction: Acute gastroenteritis (AGE) is one of the most common infectious illnesses of childhood. While no treatment is needed for self-limited virus-induced AGE, dehydration caused by diarrhea and emesis is of great concern and should be treated vigorously. However, there is no consensus on the most appropriate electrolyte composition of intravenous fluids; therefore, according to basic protocols in our hospital which suggest hypotonic fluid therapy for AGE, investigators aimed to assess the frequency of hyponatremia in gastroenteritis patients treated with intravenous hypotonic fluid therapy. Materials and Methods: This descriptive observational study was conducted at 17 Shahrivar Pediatrics Hospital between September 2008 and January 2011. The patients’ medical records were assessed and children aged between 1 month and 14 years with a diagnosis of gastroenteritis and dehydration were enrolled in the study. According to sodium concentration at T0, patients were divided into three groups: hyponatremic, hypernatrmic and isonatremic. The blood samples were analyzed for the sodium concentration at T0 and during 24 hours. Statistical analyses were performed by T test and chi-square using SPSS18 and statistical significance was defined as a p-value less than 0.05. Results: The mean age of the participants was 16.43±11.1 months; 58 patients were male (67.4%) and 28 were female (32.6%). At T0, 35 patients (40.7%) were hyponatremic, 2 patients (2.3%) were hypernatremic and 49 patients were isonatremic. Sodium concentration in the hyponatremic and isonatrmic group were 137.25±1.9 and 138.29±2.04 mEq/L respectively which showed a significant difference (p=0.028). Conclusions: Our study showed that increased sodium intake could decrease acquired hyponatremia. It seems that hyponatremia could be prevented by administering high sodium concentration fluids. Keywords: Hyponatremia; Gastroenteritis; Hypotonic Solution; Intravenous Infusion